Island Biogeography of Cryoconite Hole Bacteria in Antarctica's Taylor Valley and Around the World - Darcy, John L.; Gendron, Eli M. S.; Sommers, Pacifica; Porazinska, Dorota L.; Schmidt, Steven K. (Frontiers in Ecology and Evolution, 2018)
Cryoconite holes are holes in a glacier’s surface caused by sediment melting into the glacier. These holes are self-contained ecosystems that include abundant bacterial life within their sediment and liquid water, and have recently gained the attention of microbial ecologists looking to use cryoconite holes as “natural microcosms” to study microbial community assembly. Here, we explore the idea that cryoconite holes can be viewed as “islands”, in the same sense that an island in the ocean is an area of habitat surrounded by a barrier to entry. In the case of a classic oceanic island, the ocean is a barrier between islands, but in the case of cryoconite holes, the ocean is comprised of impermeable solid ice. We test two hypotheses, born out of island biogeographic theory, that can be readily applied to cryoconite hole bacteria. First, we ask to what extent the size of a cryoconite hole is related to the amount of bacterial diversity found within it. Second, we ask to what extent cryoconite holes exhibit distance decay of similarity, meaning that geographically close holes are expected to harbor similar bacterial communities, and distant holes are expected to harbor more different bacterial communities. To test the island size hypothesis, we measured the sizes of cryoconite holes on three glaciers in Antarctica’s Taylor Valley and used DNA sequencing to measure diversity of bacterial communities within them. We found that for two of these glaciers, there is a strong relationship between hole size and bacterial phylogenetic diversity, supporting the idea that cryoconite holes on those glaciers are “islands.” The high biomass dispersing to the third glacier we measured could explain the lack of size-diversity relationship, remaining consistent with island biogeography. To test the distance decay of similarity hypothesis, we used DNA sequence data from several previous studies of cryoconite hole bacteria from across the world. Combined with our Taylor Valley data, those data showed that cryoconite holes have strong spatial structuring at scales of one to several hundred kilometers, also supporting the idea that these dirty holes on glaciers are really islands in the cryosphere.